PENATALAKSANAAN RADIOGRAFI THORAX PEDIATRIK INDIKASI DENGUE HAEMORRHAGIC FEVER DI RS GRAHA JUANDA - Dea Fadila; Nursama Heru Apriantoro; Ekaputra Syarif Hidayat (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2022)
Thorax examination with Dengue Haemorrhagic Fever (DHF) in pediatrics generally indicates Pleural Effusion in the lungs. In the Radiology Installation of Graha Juanda Hospital, Bekasi, this case only uses AP and RLD projections. This study's purpose is to explain the thorax examination procedure in cases of Dengue Haemorrhagic Fever, the reason for using AP and RLD projections, and when the patient is tilted to the right for 5 minutes. This research is a case study with a qualitative description through direct observation in the field. The data collection method uses primary data with cases of dengue hemorrhagic fever in pediatrics. The author took subjects three years old with a thorax examination in cases of Dengue Haemorrhagic Fever with AP and RLD projections. The results of the study seen in the sample are the presence of Pleural Effusion which is one of the most frequent indications found in cases of Dengue Haemorrhagic Fever. The experiment's results on the radiographic examination appeared to be visible fluid and air boundaries in the patient's lung area.